Pits Transporting System from Pitter Fruit Machine - Case Study - Nowakowski, Lukasz; Kurp, Piotr; Skrzyniarz, Michal; Blasiak, Slawomir; Depczynski, Wojciech (Communications - Scientific Letters of the University of Zilina, 2024)
The paper presents the construction and technological aspects of a device for pitting fruit, especially cherries, on an industrial scale. The presented work includes design solutions related to the transport of pits removed from pitted fruit, as well as a gravity chute, with an indication of potential operational problems related to the machine design. The authors proposed the use of a screw conveyor, especially in the case of longer drums, to optimize the process. Some analyses are also presented, including friction occurring during the transport of pits. Ultimately, a specific design concept is presented that integrates the screw conveyor with the pitting drum. The presented conclusions point to practical technological and engineering aspects related to fruit processing, suggesting the potential for innovative solutions in the design of pitters.
Keywords: pits transport; stone transport; screw conveyor